Factors Affecting Vaccine Distribution Activities For The Community With Door To Door Method - Chatarina Hatri Istiarini; Resta Betaliani Wirata; Nurlia Ikaningtyas; Ratna Puspita Adiyasa ((JKG) Jurnal Keperawatan Global, 2022)
Background: The "pick up the ball" system requires distribution facilities such as vehicles and special storage areas that guarantee the quality of vaccines, using the door-to-door method to speed up and reach more residents who need to get vaccinated directly at the home of the vaccine participant. Methods: A cross-sectional study with a retrospective approach. This study collected data in 2 districts in Yogyakarta's special regency: the Kulon Progo district and the Gunung Kidul district. The sample for this study was drawn from a community of 249 vaccine recipients using random sampling.The original questionnaire for the factors was used. The pilot study results for the validity and reliability test for the original questionnaire showed that the validity of each statement was 0.4409 and the reliability was 0.772. A chi-square test was employed for data analysis. Results: It was found that the participant's age, occupation, knowledge, and education level have no relationship with the activity of vaccination distribution. One factor has a relationship with the activity of vaccination distribution, namely the vaccine schedule factor with an OR value of 1,205. Conclusion: The factor affecting the activity of distributing the COVID-19 vaccine was the respondent's schedule, while the factor that had no relationship was the participant's age, occupation, knowledge, and education level. Health workers can maximize the performance of the COVID-19 vaccination by using the door-to-door method by paying attention to the community's schedule.